Pragmatic marker to in Hausa (West Chadic, A.1; Nigeria) - Zając, Patryk (LingBaW. Linguistics Beyond and Within, 2024)
In Hausa language function words contribute to sentence structure mainly on the syntactic level. They can specify the attitude or mood of the speaker. The broad class of function words includes a sub-class of items known as Pragmatic Markers (PMs). So far interpretations of PM to in Hausa were based on its semantic rather than structural contributions to the utterance content. There is a lack of a closer look on to from the pragmatic perspective. The aim of this article is to demonstrate how the interpretation of to within the framework of PM can contribute to describing this item’s functions in discourse in a more precise way, i.a. for the purpose of preparation of resources for studying the Hausa language by foreigners such as bilingual dictionaries. I propose the interpretation of to as a PM with the binary category of procedural and representational meaning. It will be demonstrated with the examples extracted from radio conversations that PMs framework allows to comprehensively describe to marker in terms of its contextually determined functions and meanings.